Effect of mud drying temperature on surface characteristics of a polycarbonate PV protective cover. (February 2017) - Yilbas, B.S.; Ali, H.; Al-Sulaiman, F.; Al-Qahtani, H.
Highlights: Water condensate forms mud solution on PV cover surface under gravity. Dry mud solution forms crystals and increases dry mud adhesion on PV cover surface. Mud restudies on PV cover surface results in irregular friction coefficient behavior. Optical transmittance of PV cover reduces due to mud adhesion and surface deformation. This reduction increases over 25% for high mud drying temperatures. Abstract: Chemo-mechanical characteristics of mud formed on polycarbonate PV cover are studied in relation to solar photovoltaic applications. Mud is formed from environmental dust and water condensate mimicking humid air conditions. Effect of mud drying temperature on chemo-mechanical and optical characteristics of mud-polycarbonate interface is investigated. Mud drying temperatures are set in the control chamber according to daily temperature distribution in Dammam area. Dry mud is later removed from surfaces, by pressurized distilled water, and mud residues left over on polycarbonate surface are examined. Analytical tools including scanning electron and atomic force microscopes, energy dispersive spectroscopy, X-ray diffraction, Fourier transform infrared spectroscopy, and inductively coupled plasma mass spectrometry are incorporated for the characterization of mud solution, dry mud, and polycarbonate surface after dry mud removal. Adhesion work required to remove dry mud from polycarbonate surface is also determined from scratch tests data. It is found that alkaline (Na, K) and alkaline earth metals (Ca) compounds in dust particles dissolve in condensed water while forming chemically active mud solution, which settles at the interface between mud and polycarbonate surface under the gravity. This has a detrimental effect on cleaning of dusted polycarbonate surface because of mud solution, upon drying, increases adhesion between dry mud and surface as well as modifies microhardness and surface texture of polycarbonate surface. Mud residues left over on surfaces alters the friction coefficient of polycarbonate surface, which is more pronounced for the case in which drying temperature is high.